Spa33, a Cell Surface-Associated Subunit of the Mxi-Spa Type III Secretory Pathway of Shigella flexneri, Regulates Ipa Protein Traffic - Schuch, Raymond (American Society for Microbiology, 2001)
The Mxi-Spa type III secretion system of Shigella flexneri directs the host cell contact-induced secretion of a set of invasins, referred to as Ipas. In this study, we examined the role of Spa33 in Ipa secretion. A spa33-null mutant was both noninvasive and unable to translocate the Ipas from inner membrane to outer membrane (OM) positions of the Mxi-Spa transmembrane channel. Spa33 was found to be a Mxi-Spa substrate that is translocated to the bacterial cell surface upon the induction of Ipa secretion. This mobility may serve to drive Ipa translocation within Mxi-Spa toward OM positions. Consistent with a second distinct role in regulating Ipa traffic, the overexpression of Spa33 also blocked Ipa secretion and resulted in Ipa accumulation at the OM. Co-overexpression of Spa33 and another OM-associated element, Spa32, did not disrupt Ipa secretion, suggesting an interaction between the two proteins and an effect on the mechanism which serves to regulate Ipa release from the OM. These findings indicate that Spa33 is a mobile element within Mxi-Spa, which is required to control Ipa translocation into and out of OM positions of the secretory structure.